"n Kerk met karakter: Die perspektief van Gerben Heitink - Dreyer, Theuns F. J. (HTS teologiese studies, 2009)
A church with character: The perspective of Gerben HeitinkMainstream churches worldwide are experiencing a decline in membership. The wellknown Dutch practical theologian Gerben Heitink’s (2007) latest book Een kerk met karakte, Tijd voor heroriëntatie is an attempt to address this phenomenon. This article is an overview of his book, with comments from other authors. Although emerging churches is constitute a movement separate from the institutional churches, Heitink still takes the existing church as point of departure. He suggests a process of reorientation and transformation within based on a matrix of eight critical factors. In conclusion, the article evaluates Heitink’s model from a personal perspective within the context of the Netherdutch Reformed Church of Africa.